THE USE OF OPERATIONAL-SEARCH MEASURES IN COMBATING CYBERCRIMES - Kamilov, Timur Yusupjanovich (Oriental Journal of History, Politics and Law, 2026)
This article examines the role and significance of operational-search measures in combating cybercrime. The legal and methodological foundations of organizing and conducting operational-search activities in the context of the growing use of information and communication technologies for criminal purposes are analyzed. The article considers the main operational-search measures used in detecting and investigating cybercrimes, the procedure for their conduct, issues of collecting and consolidating digital evidence, as well as foreign experience and existing problems in the legislation of the Republic of Uzbekistan in this area. Practical recommendations have been developed based on the research results.